A Bottom‐Up and Templateless Process for the Elaboration of Plasma‐Polymer Nanostructures. Issue 2 (3rd June 2015) - Zaitsev, Andrii; Poncin‐Epaillard, Fabienne; Lacoste, Ana; Debarnot, Dominique
Abstract : In this paper, the transition from smooth layer to nanostructured one during plasma deposition of polyaniline is demonstrated. The deposition mechanism at low discharge power allows obtaining a smooth layer with well‐defined chemical structure while high discharge power gives a structured layer but does not preserve the monomer structure. A method giving the possibility to overcome these problems by combination of high‐ and low‐power deposition is described. Obtained layers are investigated by FT‐IR spectrometry, profilometry, and atomic force microscopy. Abstract : A plasma process for the elaboration of polymer nanostructures while preserving monomer chemical structure is presented. This method is based on the variation of the input power in the plasma phase during the synthesis. It allows obtaining a structured surface with high conservation of monomer structure which is necessary for practical applications.